Contributions of print exposure to first and second grade oral language and reading in Chile. (29th September 2016) - Strasser, Katherine; Vergara, Daniela; del Río, M. Francisca
Abstract : This study examines the contribution of print exposure to oral language (expressive vocabulary and listening comprehension) and reading (word reading and reading comprehension) in first and second grade in Chile, and tests whether the contribution of print exposure to reading comprehension is mediated by language and word reading skills. Two‐hundred and eighty one children (mean age 6.55 years) participated. Print exposure was measured with a book‐cover recognition task in first grade, and outcomes were measured both in first and second grade. Print exposure had direct effects on all outcomes in first grade and indirect effects in second grade. Effects on first grade reading comprehension were partially mediated by listening comprehension and word reading, but not vocabulary. We discuss the importance of the findings for improving reading comprehension in countries with low access to books.